(untitled) (Annals of Medical Research, 2025)
Aim: To determine the density ranges to evaluate the degree of hepatosteatosis on computed tomography (CT) grades. Materials and Methods: Patients who were diagnosed with hepatosteatosis by ultrasonography and those who subsequently underwent tomography were included in the study. Measurements were made from each segment of the liver and the spleen in the CT images of the graded groups. Liver/spleen density ratios were compared. Results: In total 666 patients were included for evaluation in the present study. Liver/spleen density ratios for Grade 1, Grade 2, and Grade 3 were 0.94 ± 0.19, 0.70 ± 0.16, and 0.37 ± 0.13, respectively. There was a statistically significant difference in the Liver/spleen density ratios throughout all grades (p=.001). The cut-off value separating Grade 1 and Grade 2 was calculated as 0.77, and the cut-off value separating Grade 2 and Grade 3 was calculated as 0.47. Segment 1, which had the least fat accumulation, was significantly different from all the other segments. Conclusion: In the present study, it was determined that both contrast-enhanced and non-contrast-enhanced tomography can be used for the evaluation of hepatosteatosis. However, contrast-enhanced tomography has been found to distinguish Grade 1 from Grade 2 more effectively than unenhanced CT.